O desafio de reconhecimento do sujeito cego em espaços públicos de representação - Figale, Juliana Marques (2009)
This work is funded based on the uneasiness with the concept of State as a public machine for development. Of State as a public machine to deliberate valid practices for valid methods and to limit valid subjects in valid spaces. In midst of this specific context, this work dedicates itself to investigate the following research problem: the mistaken recognition of the blind subject in public spaces of representation. For this reason, it was addressed the following question: how the blind subject is recognized in public spaces of representation? To answer the question, it was necessary to contextualize how the blind subject is being recognized in various public spaces of representation. In the international scope, the human rights debate held between the National States was analyzed (BRAND, 2005; KOERNER, 2002; UN, 2006). In the national arena, constitutional rights, federal laws, public policies and institutions representing the blind subject were examined (CABRAL, 2008; SARAVIA, 2006). Finally, in a local context, the fundaments of the concept of citizen for the subject recognition were investigated (AGAMBEN, 2002; RORTY, 1999, DELEUZE AND GUATTARI, 1996). The methodology included reports of national and international representatives in the Lusophone Countries Meeting for Dissemination and Implementation of the Convention on the Rights of Persons with Disabilities and, mainly, interviews with blind subjects. The data was processed by content analysis and was discussed based on the following categories: representation spaces; representation modes; representation amplitude; representation premises. The results show, regarding such spaces of representation, the growing importance of thinking the rights of persons with disabilities ¿ group in which belongs the blind subject ¿ as of the international and national scenario. However, the blind subjects announced alternative local spaces for representation: church, internet, radio, etc. Regarding the representation modes, the role of law and standards has been advocated specially in the human rights field. The importance of the cooperation between the States and the civil society to ensure, in practice, the rights achieved was also emphasized. But other forms of representation, directly linked to each interviewee¿ history, was important. Regarding the representation amplitude, there were arguments in defense of a conception of human dignity and freedom to all inhabitants of the globe. The lusophone event highlighted the concern of the cultural peculiarities of those involved in the meeting. The blind interviewees argued for citizenship as construction of instruments for freedom and autonomy, but recognized that this is not a clear desire between the blind people in general, and even less in society as a whole. With respect to the representation premises, the fundaments for the recognition of the blind subject were based on the primacy of reason at the expense of personal experimentation. Experimentation that serves as the foundation of a new form of recognition of the blind subject in public spaces of representation, one more interested in singularities, impenetrable by reason, unmovable to another, and which are irreducible to each subject. The final considerations suggest that if the State has a reason to be, this is not another than to offer instruments to manifest as many as the existential possibilities of the subject. This is the concept of State for development.